"Hey, I Can Do This!" The Benefits of Conducting Undergraduate Psychology Research for Young Adult Development - H. Russell Searight; Susan Ratwik; Todd Smith (Park University, 2010)
Many undergraduate programs require students to complete an independent research project in their major field prior to graduation. These projects are typically described as opportunities for integration of coursework and a direct application of the methods of inquiry specific to a particular discipline. Evaluations of curricular projects have usually found that they positively impact students' knowledge and skills in that discipline. However, little attention has been devoted to the impact that these projects have on broader aspects of psychosocial development. The current study describes the results of a focus group conducted with students who had recently completed their senior research project in psychology. Results of the focus group interview were transcribed and coded according to grounded theory principles. Five developmentally-specific categories emerged from the analysis. These included a greater sense of competence attributed to completing a large-scale project, an experience of being in a professional role relative to research participants as well as to the audience presented with their study results, and a sense of ownership and pride in completing their project. Universities that either require or are contemplating requiring senior projects should consider these broader benefits to young adult development